Resistance and virulence factors of Escherichia coli isolated from chicken - Pavlickova, Silvie; Dolezalova, Magda; Holko, Ivan (Journal of environmental science and health. Part B, Pesticides, food contaminants, and agricultural wastes, 2015)
Chicken meat has become an important part of the human diet and besides contamination by pathogenic Escherichia coli there is a risk of antibiotic resistance spreading via the food chain. The purpose of this study was to examine the prevalence of resistance against eight antibiotics and the presence of 14 virulence factors among 75 Escherichia coli strains isolated from chicken meat in the Czech Republic after classification into phylogenetic groups by the multiplex PCR method. More than half of strains belonged to A phylogroup, next frequently represented was B1 phylogroup, which suggests the commensal strains. The other strains were classified into phylogroups B2 and D, which had more virulence factors. Almost half of all E. coli strains were resistant to at least one of eight-tested antibiotics. A multidrug resistance was observed in 13% of strains. The most prevalent virulence genes were iucD, iss and tsh. None of genes encoding toxins was detected. Most of E. coli strains isolated from chicken meat can be considered as nonpathogenic on the basis of analysis of virulence factors, antibiotic resistance and phylogroups assignment. It can provide a useful tool for prediction of a potential risk from food contaminated by E. coli.
Keywords: kur domácí; Animals; Česká republika; Drug Resistance, Multiple, Bacterial; Food Microbiology; Phylogeny; Virulence Factors; potravinářská mikrobiologie; maso; zvířata; fylogeneze; Czech Republic; Escherichia coli; Chickens; Meat; mnohočetná bakteriální léková rezistence; faktory virulence